2022
DOI: 10.1111/dom.14711
|View full text |Cite
|
Sign up to set email alerts
|

Types of diet, obesity, and incident type 2 diabetes: Findings from the UK Biobank prospective cohort study

Abstract: Aim To investigate the associations between types of diet and incident type 2 diabetes and whether adiposity mediated these associations. Materials and Methods In total, 203 790 participants from UK Biobank (mean age 55.2 years; 55.8% women) without diabetes at baseline were included in this prospective study. Using the dietary intake data self‐reported at baseline, participants were categorized as vegetarians (n = 3237), fish eaters (n = 4405), fish and poultry eaters (n = 2217), meat eaters (n = 178 004) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Metabolic alterations linked to insulin resistance and decreased muscle mass probably play a crucial role. For instance, Boonpor et al have recently described this phenomenon in a prospective cohort that identified an increased risk of developing CVD in individuals with diabetes and sarcopenia 30 . Moreover, both in obesity and diabetes, dietary choices and lifestyles play a decisive role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic alterations linked to insulin resistance and decreased muscle mass probably play a crucial role. For instance, Boonpor et al have recently described this phenomenon in a prospective cohort that identified an increased risk of developing CVD in individuals with diabetes and sarcopenia 30 . Moreover, both in obesity and diabetes, dietary choices and lifestyles play a decisive role.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Boonpor et al have recently described this phenomenon in a prospective cohort that identified an increased risk of developing CVD in individuals with diabetes and sarcopenia. 30 Moreover, both in obesity and diabetes, dietary choices and lifestyles play a decisive role. In this context, the role of public policies becomes fundamentally important.…”
Section: Variablesmentioning
confidence: 99%
“…Whilst the interrelationship between dietary pattern and sociodemographic characteristics warrants further investigation it is clear that affordability of novel PBMAs is a key consideration when it comes to their adoption across a range of consumer segments (74,81,82,(88)(89)(90)(91) .…”
Section: Costmentioning
confidence: 99%
“…Inconsistency in findings may be the result of variation across consumer subgroups (74,76) , with rural consumers less influenced than urban consumers (98) , and personal experience of animal husbandry or limited access to large supermarkets also influencing this phenomenon (85,98) . Vegetarian and vegan consumers also tend to place greater value on the welfare of animals (54,58,63,(89)(90)(91)(92) .…”
Section: Animal Welfarementioning
confidence: 99%
“…During younger adulthood, there is a tendency to consume less fruit, vegetables, and dairy and more meat, potatoes, and sweets, which results in poor diet quality 9 11 12. Since diet quality is associated with the development of T2D, and early-onset T2D is increasing,1 13–15 it is important to know how young adults make dietary change over time, whether diabetes awareness or the age of diabetes awareness are associated with dietary quality, and what dietary changes are made when people learn of their diabetes. Existing studies are short-term, qualitative, have small samples, lower quality of evidence, start with middle-aged cohorts, or focus only on whether diet quality predicts future risk of developing diabetes and diabetes-related complications 8 15–17…”
Section: Introductionmentioning
confidence: 99%